PENGARUH KEMAMPUAN BERPIKIR KRITIS TERHADAP PENGUASAAN KONSEP MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD - Soirwan -; I Dewa Putu Nyeneng; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
Physic teachers have used cooperative learning in the learning groups to teach the material. However, student mastery of physic is still relatively low. The cooperative learning is not maximized. It makes the mastering concept of the material becomes low. This study purposes to investigate the influence toward the critical thinking skills of the students' mastery through STAD cooperative learning. This study was conducted in class IXb SMP 5 Bandar Lampung which consists of 35 students in the second semester of academic year 2012/2013 and the material is about Magnetism. The sampling technique used is purposive sampling. The analysis showed that both data were distributed normal and linear. Furthermore, to examine the effect, the researcher did the correlation test and simple linear regression. The results of this study indicated that there was an influence of critical thinking skills to students' mastery of concepts by STAD cooperative learning. The determination coefficient’s value with the correlation coefficient is 0, 49 which was included in the medium category with the regression equation positif where a and b constants are significant coefficients. Keywords: critical thinking skills, cooperative learning STAD type, mastery of concepts.